Frequency, Geospatial Distribution, and Subspecies of Echinococcus granulosus Identified in Dog Stool in Urban Public Spaces of an Endemic Area in Cusco, Peru - Miguel M. Cabada; Roberto Pineda-Reyes; Nelson Lozano-Cansaya; Beltran Jalanocca-Janampa; Martha V. Fernandez-Baca; Carol A. Castro; Alejandro Castellanos-Gonzalez; Alonso Bussalleu; Melinda B. Tanabe; Audrey Schulze; Diego Alvarez; Maria L. Morales; et al. (The American Journal of Tropical Medicine and Hygiene, 2026)
ABSTRACT. The impact of environmental contamination with Echinococcus granulosus eggs on the transmission to humans remains unknown. The control of free-roaming and stray dogs is a public health problem in urban and periurban areas of the Cusco region, such as the city of Sicuani in the Canchis province. Nearly one in four human cystic echinococcosis cases referred to tertiary hospitals in the Cusco region of Peru is referred from the Sicuani district. This study sought to determine the frequency and spatial distribution of E. granulosus DNA in dog stool collected within urban public spaces of Sicuani. We conducted a cross-sectional study using a systematic 100 × 100-meters 2 grid-based sampling design. Dog stools located at the closest point to georeferenced square vertices were selected for collection. Epidemiologically relevant locations, such as abattoirs and food markets, were also georeferenced. Nineteen (5.5%) of 347 collected samples tested positive for E. granulosus DNA. Polymerase chain reaction (PCR)-positive stools were located at a shorter median distance than negative stools to abattoirs (564 versus 1,292 meters, respectively, P